وسائل التواصل الاجتماعي والعربية الفصحى: social media, new media, arabizi, linguistic pollution - ÙØ§, Ù…Øª Ø·ÙŠØ¨; Ø¹Ø¨Ø¯ Ø§Ù„Ø¹Ø²ÙŠØ² Ø§Ù„ØØ¯Ø§Ø¯, Ø¹Ø¨Ø¯ Ø§Ù„ÙˆÙ‡Ø§Ø¨ (Al-Ḍād Journal, 2017)
This research addresses the social media in different perspectives, starting with the most prominent definitions, its origins in the mid-1990s. It highlights its benefits for individuals and societal levels, and explicates the motivation behind the movement from a real world to a virtual one. We will conclude by presenting a detailed diagnostic of the use of Arabic in social media nowadays. Thus, we will discuss three major issues: the interaction between social media and the Arabic language, the impact of social media on the language, and the linguistic changes in social media platforms.